The State of Cotton Production in the Surkhandarya Oasis During the Years of Stagnation and its Negative Impact on Socio-Economic Life - Yakubova Diloram Tadjievna (European Journal of Life Safety and Stability (2660-9630), 2024)
In the 1970s, the Soviet state continued to develop cotton growing in Surxondaryo. In the ninth five-year period from 1971 to 1975, the task was set to further increase cotton production in the region. However, to achieve this, it was necessary to establish cotton growing on newly developed lands. For this purpose, the main attention was paid to the Kyzyryk steppe. Renowned mechanicians and experienced managers were involved in the state farms established here.